1985
DOI: 10.1111/j.1365-2125.1985.tb02646.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of binodaline and amitriptyline on peripheral autonomic functions in healthy volunteers.

Abstract: Twelve healthy male volunteers participated in five experimental sessions separated by weekly intervals. At the beginning of each session the subjects received one single oral dose of the following drugs, according to a double‐blind, balanced cross‐over design: binodaline hydrochloride (50 mg or 100 mg); amitriptyline hydrochloride (50 mg or 100 mg); lactose placebo. Salivation and resting pupil diameter were assessed before and 2 h after the ingestion of the drugs; baseline sweating, carbachol‐ or phenylephri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…A decrement in performance on the digit cancellation test without any effect on the other psychomotor tests used is in agreement with a previous report from our laboratory indicating the sensitivity of the digit cancellation test in detecting psychomotor impairment (Szabadi et al, 1984). The reduction in salivation by amitriptyline is in agreement with previous observations (Szabadi et al, 1980b;Longmore et al, 1985), and is likely to reflect the antimuscarinic property of this antidepressant. The observation of a small reduction in heart rate and in resting diastolic blood pressure, without any changes in systolic blood pressure or the orthostatic response, is in general agreement with previous reports that acute single doses of amitriptyline have variable and relatively small effects on heart rate and blood pressure (see Szabadi and Bradshaw, 1986).…”
Section: Part Asupporting
confidence: 92%
See 1 more Smart Citation
“…A decrement in performance on the digit cancellation test without any effect on the other psychomotor tests used is in agreement with a previous report from our laboratory indicating the sensitivity of the digit cancellation test in detecting psychomotor impairment (Szabadi et al, 1984). The reduction in salivation by amitriptyline is in agreement with previous observations (Szabadi et al, 1980b;Longmore et al, 1985), and is likely to reflect the antimuscarinic property of this antidepressant. The observation of a small reduction in heart rate and in resting diastolic blood pressure, without any changes in systolic blood pressure or the orthostatic response, is in general agreement with previous reports that acute single doses of amitriptyline have variable and relatively small effects on heart rate and blood pressure (see Szabadi and Bradshaw, 1986).…”
Section: Part Asupporting
confidence: 92%
“…This effect of amitriptyline is in agreement with previous reports from our laboratory (Szabadi et al, 1980b;Longmore et al, 1985) and is indicative of the antimuscarinic effect of amitriptyline (see Szabadi and Bradshaw, 1986). Pilocarpine-evoked miosis was not affected by 50 mg amitriptyline, although a previous study has shown the antagonism of this response by amitriptyline (Szabadi et al, 1980).…”
Section: Part Bmentioning
confidence: 87%
“…Sibutramine was associated with small but statistically significant increases in supine HR and systolic BP, while amitriptyline caused a (non-significant) rise in standing HR in association with falls in both supine and standing systolic and diastolic BP. Amitriptyline was associated with an expected 30% decrease in salivation compared with a 30% increase with placebo (Longmore et al, 1985;Szabadi & Bradshaw, 1986) but there were no consistent changes with sibutramine. None of the drugs significantly altered pupil size.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the studies have confirmed the validity of single-dose crossover volunteer studies of salivation rate in the prediction of anticholinergic side-effects. It may, however, still be possible to refine the methods, for instance by 1) parallel prediction of individual steady-state serum drug levels from simultaneous analyses of single-dose pharmacokinetics (see, e.g., (13)), 2) correction for the proportion of reduced salivation due to alpha-I-adrenergic receptor blocking from parallel assessment of phenylepinephrine-evoked inhibition of sweating (14), or 3) identification of methods more specific of anticholinergic effects, for instance possibly methods based on measurement of variables derived from electrocardiographic recordings of heart rate variation (IS).…”
Section: Discussionmentioning
confidence: 99%